Analysis of Irrigation Network Operation and Maintenance Performance Improvement in Solok Regency - Heaby Virginaldo Vielki Pratama; Benny Hidayat; Taufika Ophiyandri (Universitas Islam Sultan Agung, 2026)
Agricultural development is one of the main priorities in supporting sustainable food security, which requires integrated resource management and adequate infrastructure support. Solok Regency is one of the regions that plays a strategic role in supporting national food security; therefore, the performance of irrigation network operation and maintenance is a crucial factor in ensuring the sustainability of agricultural production. However, the implementation of irrigation network operation and maintenance in this region still faces various challenges that potentially reduce the reliability of irrigation services. This study aims to identify problems related to irrigation network operation and maintenance, evaluate their performance, and formulate strategies to improve irrigation network performance in Solok Regency. The urgency of this study is based on the importance of improving irrigation performance as a key support for agricultural productivity and regional food security. This study employs a descriptive qualitative approach, with data collected through field observations, interviews, and document analysis in several irrigation areas. Irrigation system performance was evaluated using the ePAKSI application to obtain the Irrigation System Performance Index (IKSI), while strategy formulation was conducted using SWOT analysis supported by IFAS and EFAS analyses. The results indicate that the operation and maintenance performance of irrigation networks in Solok Regency remains in the poor category, influenced by limited budgets, physical deterioration of irrigation infrastructure, insufficient human resources, suboptimal routine maintenance, and low participation of Water User Associations (P3A). The recommended strategy for performance improvement is the Weaknesses–Opportunities (W–O) strategy, which emphasizes leveraging external opportunities to address internal weaknesses in order to achieve sustainable improvements in irrigation performance.